WEB Based Monitoring System for SFP Interface Traffic, Case Study in Riyad Network Banyuwangi - Yuliandoko, Herman; Utomo, Agus Priyo; Maulana, Ahmad Nur (Jurnal Jaringan Telekomunikasi, 2023)
PT Riyad Network Multi Teknologi is a company that provides internet services, commonly known as an ISP (Internet Service Provider), in Banyuwangi. This company uses MikroTIK as network management, which has an SFP interface. Through this SFP, the fiber optic network is connected to a router in their network. Therefore, traffic monitoring is needed to maintain and monitor the condition of the internet services provided. In addition, this company also does not have a notification system if there is a problem on their network. This research designs and implements a monitoring system through an SFP interface combined with a troubleshooting notification system. This monitoring requirement is very necessary for continuous maintenance or monitoring of the network, so research on the SFP Interface Monitoring System on Web-Based MikroTIK Routers at this company will be very useful. This monitoring system was created using the PHP framework codeigniter 3. The purpose of this system is to make it easier to see traffic monitor data and Rx/Tx power SFP. Moreover, the results and testing of the system-built show that the system can monitor well the problem occur in the network beside that the notification can inform to the maintenance team when problem occur.